10.1111/acn.v9999.9999 (CrossRef Listing of Deleted DOIs, 2000)
Background The ability to converse with others enables us to participate in everyday life. People with neurogenic communication disorders (NCDs), such as aphasia or traumatic brain injury (TBI), often experience difficulties engaging in conversation. While Systemic Functional Linguistics (SFL) has been used to analyze conversations involving people with NCDs, its application to clinical assessment and intervention remains limited. Aims The primary aim of this paper is to make the case for Systemic Functional Linguistics as a clinically useful framework for understanding, assessing, and supporting conversation in people with neurogenic communication disorders. Method We provide an overview of SFL and introduce an SFL-based framework, Discourse Structure Analysis. We review previous SFL-based studies of adult communication disorders and also describe the USeFuL Project, a multinational collaboration focused on developing SFL-based clinical tools. Finally, we present a worked clinical example illustrating how DSA can support detailed analysis of conversations involving people with and without aphasia. Main contributions SFL-based frameworks can be used systematically to guide clinical decision-making when providing services to people with neurogenic communication disorders. By enabling detailed, coded analyzes of naturalistic conversations, these approaches reveal patterns of participation that are often missed in standard assessments. Moreover, SFL can inform the development of meaningful, measurable therapy goals and the development of individualized care plans. Conclusions SFL offers a powerful, context-sensitive framework for analyzing and supporting communication in people with NCDs. By applying SFL in clinical contexts, clinicians can build more precise, functional, and person-centered interventions that enhance real-world communication. What this paper adds What is already known on this subject Systemic Functional Linguistics (SFL) is a theory of communication which examines how language users make choices to convey meaning in specific contexts. Over the past 30 years, researchers have used systemic functional linguistics (SFL)- based frameworks to study real-world conversations involving people with neurogenic communication disorders (NCDs). Researchers have investigated interactions that occur in a number of settings, focusing primarily on health care contexts. Two major themes are evident within this literature: control over how conversations play out tends to be exercised predominantly by people without communication disorders, and all participants in an interaction contribute to communicative success. What this study adds to existing knowledge We are the first group to argue for SFL-based studies that provide clinicians with conceptual frameworks and theory-informed tools they can use during all stages of clinical care including assessment, goal setting and treatment. As a first step in meeting this need, we offer an overview of discourse structure analysis (DSA, a form of SFL) and provide a worked example of how clinicians could use DSA when providing services to people with neurogenic communication disorders. Finally, we introduce the Using Systemic Functional Linguistics to Understand Neurogenic Communication Disorders (USeFuL) Project, a collaboration founded to pursue a clinical, SFL-based research agenda. What are the clinical implications of this study? People with NCDs want therapies that will improve communication abilities in the real world. Because SFL-based studies always focus on data gathered in everyday settings, this discipline could be used to develop highly functional and relevant assessments, goal setting procedures and treatments. The worked example provided in this paper illustrates some key ideas about how clinicians might go about applying DSA (a form of SFL) when working in conjunction with clients to develop and carrying out plans of care. Future studies by the USeFuL Project will build on current work and expand the SFL-informed tools and approaches available to clinicians.